DEVELOPING READING MATERIALS FOR JUNIOR HIGH SCHOOL STUDENTS BASED ON CONTENT AREA - Anggita Kasanra Lubis; Busmin Gurning; Rafika Dewi Nasution (Universitas Negeri Medan, 2017)
Reading is the basic in learning every subject. The more understanding the text, the more information students can gain. However, the reading materials that the students use is not appropriate based on syllabus. Therefore, the reading materials should be developed to fulfil the syllabus and the students' needs also. Because English is included Content Area Reading, so the development of reading materials is based on content area which focus on strengthen the vocabularies, specifically the unfamiliar ones, by giving glossary and related pictures. The developed text is only focus in the first semester which is descriptive and recount text. The research was conducted at SMP Muhammadiyah 7 Medan. The data was taken from interviewing the English teacher and distributing questionnaires for 30 students in grade VIII-4. The data showed that students need materials which is related to their environment and constructed by familiar vocabularies. Based on the result of the study, conclusion and suggestion are directed to the English teacher who is teaching in that school to provide reading materials based on syllabus and students' needs regularly. Keywords: Developing, Reading Materials, Content Area